2003
DOI: 10.1046/j.1462-5822.2003.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisinfection causes different levels of apoptosis and necrosis in human macrophages and alveolar epithelial cells

Abstract: Mycobacterium tuberculosis interacts with macrophages and epithelial cells in the alveolar space of the lung, where it is able to invade and replicate in both cell types. M. tuberculosis -associated cytotoxicity to these cells has been well documented, but the mechanisms of host cell death are not well understood. We examined the induction of apoptosis and necrosis of human macrophages (U937) and type II alveolar epithelial cells (A549) by virulent (H37Rv) and attenuated (H37Ra) M. tuberculosis strains. Apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
175
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 58 publications
6
175
0
7
Order By: Relevance
“…U937 human monocytic cell line (ATCC CRL-1593-2) and human monocyte derived macrophages were cultured as reported in ref. 33. Human monocytes were obtained from the blood of volunteers, using protocols approved by the Institutional Human Subject committee.…”
Section: Methodsmentioning
confidence: 99%
“…U937 human monocytic cell line (ATCC CRL-1593-2) and human monocyte derived macrophages were cultured as reported in ref. 33. Human monocytes were obtained from the blood of volunteers, using protocols approved by the Institutional Human Subject committee.…”
Section: Methodsmentioning
confidence: 99%
“…55 In addition, alveolar epithelial cell lines in culture are subject to necrosis by virulent but not attenuated mycobacterial organisms. 56,57 The attenuation of BCG is related to the loss of the RD1 locus encoding ESAT-6, which is responsible in part for the cytolysis of pneumocytes by virulent mycobacteria. 58 The ability of GM-CSF to prevent epithelial cytotoxicity by virulent mycobacteria early in the course of the infection, underlies the significantly reduced rate of mortality of GMOE mice.…”
Section: Discussionmentioning
confidence: 99%
“…4 Pathogen escapes killing mechanisms of toxic reactive oxygen or nitrogen intermediates by limiting phagocytic cells to generate these most effective anti-bacterial molecules. 5,6 Mtb contains molecular strategies to hijack trafficking pathways to prevent autophagy and the destruction of macrophages by apoptosis [7][8][9] that has been proposed to be the virulence characteristic of Mtb. Many manners, employed by Mtb, have been described to inhibit a macrophage self-death, [7][8][9][10][11] leading to the conclusion that this property must be an important one for the pathogen survival outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Alveolar epithelial cells are also subjected to the same destiny when infected with Mtb. 7,14 Evidence suggests that upon infection of macrophages, Mtb induces an anti-apoptotic mechanism by suppressing TNF-a-mediated extrinsic apoptosis but, concomitantly, pathogen activates the intrinsic pathway through mitochondrial damage, 11 which leads to necrosis as an exit strategy. 11,15 Experimental models have shown that the RD1 region, present in both M. tuberculosis and Mycobacterium marinum, is involved in the necrosis process and deficiency to secrete ESAT-6 and CFP-10 proteins results in impairment of both pathogen to exit macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation